Extended spectrum beta-lactamase producing enterobacteriaceae (ESBL) isolated from herbal preparations - Omoruyi, Iyekhoetin Matthew; Ogunsakin, Ayomikun (International Journal of Health, 2017)
Herbal preparations are unsuspected sources of human exposure to pathogenic microorganisms, including those showing high resistance to antibiotics. In this study, we investigated the presence of bacteria belonging to the enterobacteriaceae family in herbal preparation and for the presence of the Î²-lactamase enzyme by established methods. The mean coliform and enterobacteriaceae counts ranged from 2.3 x 103 to 1.1 x 106 cfu/ml and 2.3 x 103 to 6.5 x 104 cfu/ml respectively. The organisms were further identified to belong to the genus Escherichia, Klebsiella, Citrobacter and Serratia. The antibiogramic activity shows that the bacterial isolates were mostly resistant to caftazidime, augmentin and cefuroxime. Only one of the Klebsiella specie further elicited extended spectrum beta lactamase (ESBL) activity against the cephalosporin antibiotics. There is therefore, increased need for microbiological and toxicological examination of herbal medicine to prevent outbreak of diseases.